Acceptability and Initial Efficacy of Education for Teen Mothers. Issue 3 (May 2015) - Logsdon, M. Cynthia; Davis, Deborah Winders; Stikes, Reetta; Ratterman, Rachel; Ryan, Lesa; Myers, John
Abstract: Purpose: Educational materials used by healthcare agencies frequently do not follow national health guidelines for plain talk. Adolescent mothers are a vulnerable population in need of accurate and accessible health information to promote their own health and that of their baby. The aims of our study were to: Determine acceptability of simple, written educational pamphlets to adolescent mothers; Determine efficacy of simple, written educational pamphlets in improving an adolescent mother's knowledge related to breastfeeding, infant care, postpartum depression, and mother–infant relationship; Determine if higher knowledge scores are maintained after a 2-week period; and Determine general parenting health literacy of adolescent mothers. Study Design and Methods: Using a prospective, experimental design, students enrolled in a teen parent program ( n = 123) completed a pretest and The Parent Health Literacy Activities Test (PHLAT), read the health educational materials, and completed an immediate posttest of knowledge and acceptability. Two weeks later, the same participants completed a second posttest of knowledge. Results: Adolescent mothers found the intervention (simple, written educational materials) to be acceptable. The intervention was initially effective in improving knowledge scores in all four content areas. However, knowledge was not retained and scores were not significantly different from baseline at the 2-week assessment. The mean health literacy of the adolescent mothers was poor. Clinical Implications: A booster session may be necessary for knowledge retention. Other methods of education should be studied to evaluate efficacy for adolescent mothers' knowledge retention of important health information. Abstract : Pregnant teens are in need of education about many aspects of prenatal health, labor, birth and postpartum, and infant care. The process of learning important information about maternal-newborn care and the challenges of retaining the information over time are explored in this study. Health literacy is essential to promoting quality outcomes for mothers and babies.